(untitled) (Global Journals of Research in Engineering, 2014)
Scheduling is an important tool for manufacturing and engineering where it can have a major impact on the productivity of a process In this paper we use flow shop scheduling in KCCL Kohinoor Chemical Company Limited find out the optimum policy in scheduling operating several machines to produce soap to reduce idle time of machines Considering different type of machine that also absorbs different production time The industry tries to identify their idle time best presidential relationship between the machines We use Johnson s scheduling algorithm a numerical output is achieved